2013
DOI: 10.1145/2535917
|View full text |Cite
|
Sign up to set email alerts
|

Bringing young women into computing through the NCWIT Aspirations in Computing program

Abstract: A program to encourage and support girls and women in pursuing their computer science interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Past interventions such as high school summer camps, peer mentoring, presentations, and conferences have met with mixed success, but the reasons for those that were failures remain unclear (Craig, 2015;Downey et al, 2016;DuBow & James-Hawkins, 2016;DuBow, Farmer, Wu, & Fredrickson, 2013;Fuller, Turbin, & Johnston, 2013;Guzdial, Ericson, McKlin, & Engelman, 2014). Few studies have conducted controlled experiments to test our understanding and evaluate our underlying assumptions of past surveys and interventions, which is why we conducted our current study.…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Past interventions such as high school summer camps, peer mentoring, presentations, and conferences have met with mixed success, but the reasons for those that were failures remain unclear (Craig, 2015;Downey et al, 2016;DuBow & James-Hawkins, 2016;DuBow, Farmer, Wu, & Fredrickson, 2013;Fuller, Turbin, & Johnston, 2013;Guzdial, Ericson, McKlin, & Engelman, 2014). Few studies have conducted controlled experiments to test our understanding and evaluate our underlying assumptions of past surveys and interventions, which is why we conducted our current study.…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
“…Trying to change the stereotypes of technology work and tackling the negative image of IS work for women (Fisher et al, 2015;Fuller et al, 2013;Master, Cheryan, & Meltzoff, 2016;Whitney, Gammal, Gee, Mahoney, & Simard, 2013) 3. Providing a method of direct, focused encouragement for women by providing peers and role models (DuBow et al, 2013;Fisher et al, 2015;Guzdial et al, 2014) 4. Creating ways to share information among women (DuBow et al, 2013;Fisher et al, 2015;Payton et al, 2016a;Whitney et al, 2013), and 5.…”
Section: Interventions To Encourage Interestmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Similarly, racial and ethnic disparities persist in the STEM workforce, with Black and Hispanic women accounting for 5% of the computing and mathematical workforce in 2019. 3 These disparities are fueled by gender, racial, and ethnic stereotypes; isolation; lack of exposure; and lack of access to mentors, sponsors, and role models. 4 Notably, while there continues to be abundant growth in the biomedical informatics field, a recent study of biomedical informatics doctoral programs found that Black or African American and Hispanic students accounted for ∼3% and ∼6% of biomedical informatics-related doctoral graduates from 2002 to 2017 and that in total, Alaska Native, American Indian, Black or African American, Hispanic, Native Hawaiian, and Pacific Islander students comprised 11.7% (284/2426) of all biomedical informatics-related doctoral graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Computer occupations represent 50% of STEM employment, 5 yet according to the U.S. Department of Labor, the percentages of women in computing occupations, depending on subfield, ranges from 9-47% in 2009, with the field of computer hardware engineering at 9%. 7 While women are notably underrepresented in the professional computing field, the number of female award recipients is below their overall representation. For the A.M. Turing Award, the Association for Computing Machinery's (ACM) most prestigious award, only 7% of the awards have been made to women.…”
Section: Rewards and Recognitionmentioning
confidence: 99%